Altered resting-state voxel-level whole-brain functional connectivity in multiple system atrophy patients with cognitive impairment. Issue 1 (January 2020) - Yang, HuaGuang; Luo, XiaoGuang; Yu, HongMei; Guo, MiaoRan; Cao, ChengHao; Li, YingMei; Fan, GuoGuang
Highlights: Abnormal functional networks are identified in patients with multi-system atrophy. MSA patients with cognitive impairment (CI) showed a DC decrease in the RMPFG. Decreased RMPFG-DMN and insula functional network are correlated with CI in MSA. Abstract: Objective: There is increasing evidence of cognitive impairment (CI) frequently occurring in patients with multiple system atrophy (MSA); however, the neurobiological mechanisms underlying CI in patients with MSA remain unclear. Methods: We enrolled 61 patients with probable MSA and 33 healthy controls (HC). We used degree centrality (DC) analysis to assess changes in the centrality level of MSA-CI related brain nodes. We conducted a secondary seed-based functional connectivity (FC) analysis to investigate dysfunctions in cognitive networks related to MSA. Further, we analysed the correlation between clinical symptoms and acquired connectivity measures. Results: Compared with HC, patients with MSA-CI and those with MSA with normal cognition (MSA-NCI) exhibited lower DC values in the left calcarine and right postcentral regions and higher DC values in the bilateral caudate and left precuneus. There were significant differences in the DC values in the right middle prefrontal gyrus between the MSA-CI and MSA-NCI groups. The mean DC values in the right middle prefrontal gyrus (RMPFG) were correlated with clinical cognitive severity. Consequently, we used this brain region as a seed in secondary seed-based FC analysis and observed FC changes within the right precuneus, inferior parietal lobe, and right insula. Conclusions: Decreased middle prefrontal cortex activity and its altered functional connectivity with the precuneus, inferior parietal lobe, and insula are possible biomarkers of cognitive dysfunction in patients with MSA-CI. Significance: Cognitive impairment in MSA is associated with alterations in the dorsolateral prefrontal cortex network.